USING INSTAGRAM SOCIAL MEDIA AS A MEDIA OF INTERACTION IN SHAPEING THE TEENAGE'S LIFESTYLE - Julius Caesar Transon Simorangkir (SEAN Institute, 2021)
This study was conducted to determine the use of social media Instagram in shaping the lifestyle of teenagers in Kutamandiri Village. The method used is descriptive research that uses a qualitative approach. Based on the research results, Instagram is the dominant social media used by teenagers. Instagram has a very interesting feature so that teenagers often interact on Instagram. The results of this study are Instagram can shape the lifestyle of teenagers, because Instagram provides access for teenagers to express themselves freely in public. Teenagers' lifestyles change and they are formed from their interests and interests with lifestyles that become a place to exist for others.